Cluster and forecasting analysis of the residential market in Turkey An autoregressive model-based fuzzy clustering approach - Vatansever, Metin; Demir, Ibrahim; Hepsen, Ali (EMERALD GROUP PUBLISHING LTD, 2019)
Purpose The main purpose of this study is to detect homogeneous housing market areas among 196 districts of 5 major cities of Turkey in terms of house sale price indices. The second purpose is to forecast these 196 house sale price indices. Design/methodology/approach In this paper, the authors use the monthly house sale price indices of 196 districts of 5 major cities of Turkey. The authors propose an autoregressive (AR) model-based fuzzy clustering approach to detect homogeneous housing market areas and to forecast house price indices. Findings The AR model-based fuzzy clustering approach detects three numbers of homogenous property market areas among 196 districts of 5 major cities of Turkey where house sale price moves together (or with similar house sales dynamic). This approach also provides better forecasting results compared to standard AR models by higher data efficiency and lower model validation and maintenance effort. Originality/value There is no previous research paper focusing on neighborhood-based clusters and forecasting house sale price indices in Turkey. At this point, it is the first academic study.
Keywords: Forecasting; House price index; Fuzzy model; Model-based time series clustering; Turkish housing market; Visual cluster validity; HOUSING-MARKET; SEGMENTATION; PERFORMANCE; Urban Studies